(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Through this article, the formation of a civil duty, a sense of personal responsibility, a sense of belonging to the fate of the motherland, an active life position and a firm belief, professional skills in them by educating students of the direction of military education up to the call.